(untitled) (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2023)
Cow ghee is a nutritious food with a lot of health benefits and popular ingredient in many vegetarian diets and indigenous medical formulations. Due to high demand, the adulteration of cow ghee with more affordable and widely available vegetable oils and animal fat is common in many industries. The detection of adulteration by instrumental techniques is expensive and time-consuming. Therefore, simple, rapid and cost-effective tests are essential for the detection of adulterants in cow ghee. The aim of this study was to compare the physicochemical parameters of pure cow ghee with the market samples using the SLS 313 and detection of adulteration using chromogenic tests and conformation through GC-MS. A pure cow ghee sample (S-01) was prepared from the curd made in the laboratory. Thirteen market samples (S-02 to S- 14) were purchased from Northern, Southern, Western and Central provinces and analyzed for physicochemical parameters (moisture and volatile matter content, relative density, refractive index, acid value, iodine value, saponification value and peroxide value) based on SLS 313 standard protocols. As chromogenic tests, Modified Salkowski, and furfural tests were followed. In the Modified Salkowski test, the pure sample observed a red colour, whereas the adulterated samples showed a reddish brown to dark brown colour. The pure sample showed no colour in the furfural test, while the adulterated sample showed a light pink to crimson red. In conclusion, eleven market samples (from S-02 to S-12) were adulterated in different levels with edible oils and GC-MS analysis confirmed the adulterants and the chemical composition variation from the pure cow ghee samples. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">